Design and fabrication of a generic 3D-printed silicone unilateral cleft lip and palate model - Riedle, Hannah; Burkhardt, Andrea E.; Seitz, Vera; Pachaly, B.; Reid, Russell R.; Lee, Justine C.; Franke, Jörg (Journal of Plastic Reconstructive and Aesthetic Surgery, 2019)
The complexity of plastic surgery procedures often requires visualization of the anatomy in three dimensions and therefore demands the development of new and innovative teaching methods. This work describes the development and manufacture of a 3D silicone cleft lip and palate (CLP) model evaluated by surgical residents on its similarity to the biological model. Thirty unilateral CLP models were created and distributed to residents at two different institutions. The model was based on an adult CT scan that was manipulated to resemble an infant with a complete unilateral CLP. This digital model was directly printed in silicone elastomer pieces and later assembled. The residents rated the model based on its realistic value as well as whether or not they felt it improved their surgical technique. Twenty residents used the model to simulate a CLP repair. The structure of the model was rated as fairly realistic while both the material and assembly of the model require improvement in subsequent manufacturing. Post simulation, residents rated the model highly for how accurately it simulated the surgical procedure. An accurate 3D silicone unilateral cleft lip and palate replica was successfully created for educational purposes. This new approach combines a flexible generic design with automated manufacture.
CRIS-Team Scopus Importer:2019-08-30
Keywords: Cleft lip; Infant; Models; Reconstructive surgical procedures; Silicone elastomer; Surgery; plastic

Design and Fabrication of a Multi-Material Neurosurgical Simulator for an Endoscopic Third Ventriculostomy - Riedle, Hannah; Wittmann, Peter; Franke, Jörg; Rössler, Karl (BMEiCON 2019 - 12th Biomedical Engineering International Conference, 2019)
Haptic surgical simulators can improve skills and knowledge through experience. One possible application is the training of the high-risk procedure of an endoscopic third ventriculostomy (ETV) to treat an occlusive hydrocephalus. This study presents the development of a neurosurgical simulator optimized for automated manufacturing, while maintaining anatomical details and a variety of material properties. The core of the simulator is a 3D printed silicone model of the ventricular system, embedded in soft silicone gel, simulating the brain matter. Hard anatomical elements and a dynamic body fluid system complete the setup. The evaluation of the simulator by a medical expert shows that the anatomical geometries are realistic; the material properties however still need improvement.
CRIS-Team Scopus Importer:2021-04-20
Keywords: 3D printing; anatomical model; modelling; neurosurgery; surgical simulation

Determination of the Mechanical Properties of Aortic Tissue for 3D Printed Surgical Models - Riedle, Hannah; Mukai, Barbara; Molz, Pirmin; Franke, Jörg (BMEiCON - 2018, 2018)

Determination of the Mechanical Properties of Cardiac Tissue for 3D Printed Surgical Models - Riedle, Hannah; Molz, Pirmin; Franke, Jörg (2018 IEEE-EMBS CONFERENCE ON BIOMEDICAL ENGINEERING AND SCIENCES (IECBES), 2018)
CRIS-Team WoS Importer:2019-02-27

Experimental determination of the suture behavior of aortic tissue in comparison to 3D printed silicone modelling material - Riedle, Hannah; Chaban, Ryan; Ghazy, Ahmed; Piplat, Charlotte; Dorweiler, Bernhard; Franke, Jörg (Journal of the Mechanical Behavior of Biomedical Materials, 2020)
The imitation of biological tissue in a synthetic physical model can benefit many medical applications, e.g. pre surgical planning or education. For a quantitative validation of the model's mechanical behavior, standardized testing on both, the biological original and the artificial material, is necessary. In four parts, this study focuses on the biomechanical analysis of the impact of sutures for aortic modelling using 3D printed silicone. Testing methods are developed and executed on biological and synthetic samples. The first part is the determination of the pullout strength of a single stitch. The second part is the investigation of the reduction of the tensile strength and elongation of tensile bars due to stitching. Third, the tensile testing of biological and artificial vessels repaired with an anastomosis gives information about the transferability to real surgical applications. A qualitative feedback study with surgical experts concludes the evaluation. The study reveals that the pullout strength is independent from the fiber or notch direction, but that repaired aortic tensile bars show a dependency on the fiber direction of the tissue. Additionally, the circular seam of the anastomosis provides a more stable connection than multiple single stitches. For the artificial models, the mechanical behavior mainly depends on the mechanical properties of the base silicone, here represented by the Shore A hardness, rather than the manufacturing process. When compared to the biological original the most similar material varies depending on the mechanical property in focus.
CRIS-Team Scopus Importer:2020-09-11
Keywords: 3D printing; Anatomical models; Aorta; Silicone; Suture

Experimental Mechanical Examination of Artificial 3D Printed and Post Processed Vascular Silicone Models * - Riedle, Hannah; Braunias, Kim; Mukai, Barbara; Franke, Jörg (2019 41st Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC), 2019)

Generation of 3D Silicone Models of Anatomic Soft Tissue Structures - A Comparison of Direct 3D Printing and Molding Techniques - Riedle, Hannah; Seitz, Vera; Schraudolf, Larissa; Franke, Jörg (2018 IEEE-EMBS CONFERENCE ON BIOMEDICAL ENGINEERING AND SCIENCES (IECBES), 2018)
CRIS-Team WoS Importer:2019-02-27

Generic design of an anatomical heart model optimized for additive manufacturing with silicone - Riedle, Hannah; Ghazy, Ahmed; Seufert, Anna; Seitz, Vera; Dorweiler, Bernhard; Franke, Jörg (Rapid Prototyping Journal, 2020)
Purpose: The purpose of this study is the generation of a thorough generic heart model optimized for direct 3D printing with silicone elastomers. Design/methodology/approach: The base of the model design is segmentation of CT data, followed by a generic adaption and a constructive enhancement. The model is 3D printed with silicone. An evaluation of the physical model gives indications about its benefits and weaknesses. Findings: The results show the feasibility of a generic design while maintaining anatomical correctness and the benefit of the generic approach to quickly derive a multiplicity of healthy and pathological versions from one single model. The material properties of the silicone model are sufficient for simulation, but the results of the evaluation indicate possible improvements, as for most anatomical features, the used silicone is too hard and too stretchable. Originality/value: Previous developments mostly focus on patient-specific heart models. In contrast, this study sets out to explore the possibility and benefits of a generic approach. Standardized validated models would allow comparability in surgical simulation.
CRIS-Team Scopus Importer:2020-12-25
Keywords: 3D printing; Generic design; Heart model; Medical education; Silicone; Surgical simulation

Letter of Response Re: Design and fabrication of a generic 3D printed silicone unilateral CLP model - Riedle, Hannah; Lee, Justine C.; Franke, Jörg (Journal of Plastic Reconstructive and Aesthetic Surgery, 2019)

Matching of Mechanical Properties of Biological Tissues and Technical Materials for the Fabrication of Anatomical Models by Material Jetting - Preis, Alexander; Riedle, Hannah; Benke, Elisabeth; Franke, Jörg (Proceedings of the 14th International Joint Conference on Biomedical Engineering Systems and Technologies - Volume 1: BIODEVICES, 2021)
Realistic, high-fidelity anatomical models with material properties corresponding to those of human tissue can be used for surgical planning and training, medical education and medical device testing and validation. Conventional manufacturing of anatomical models is a time consuming, and expensive process, which nevertheless is not able to fully mimic the complex nature of the human body regarding geometry and mechanical properties. To create models closer to reality in a fast and cost-effective way, additive manufacturing, especially the process of material jetting, can be a solution. Utilizing this process, it is possible to fabricate multi-color, multi-material objects with complex geometries, high resolution, and even gradients in material properties. To replicate the mechanical properties of biological tissues, they must be matched with the technical materials or material combinations available for the utilized manufacturing process. Therefore the authors propose to conduct measu rements according to standardized testing procedures like ISO 37 for tensile and ISO 48-4 for indentation tests, which allows matching to the manufacturing materials and thus will result in the possibility to create more accurate replicas of the human body that provide realistic haptic feedback.<br
Keywords: Surgical Models; Anatomical Models; Surgical Training; Medical Education; Medical Device Evaluation; Biomechanics; Biomechanical Testing; Additive Manufacturing; 3D Printing; Material Jetting; Standardization